Proceso de atención de enfermera en neonato con dificultad respiratoria. - Herrera Velasco, Naila Azucena (2020)
The present work was based on the nursing care process of a preterm newborn female of 31 weeks of gestation with a clinical diagnosis of respiratory distress syndrome, which is a very common pathology in neonates, for which it is intended to classify the different problems detailed in the newborn in order to carry out the appropriate nursing actions to improve their health. The main objective of this investigative case study is to apply the nursing care process in a newborn with respiratory distress by which the altered needs are identified, correct and rehabilitate the patient through the application of nursing knowledge, procedures and interventions. A nursing plan was planned according to the most significant needs of the newborn in order to verify if the nursing interventions carried out helped improve the newborn's health.